تقويم برنامج "عربيتي" في إكساب مفردات اللغة العربية لدى الدارسين الناطقين بغيرها = Taqwim barnamij 'arabiyyatiyy fi iksab mufradat al-lughat al-'arabiyyah lada al-darisin al-natiqin bi-ghayriha - Zainuddin, Nurkhamimi; Sahrir, Muhammad Sabri; Nasir, Mohd Shahrizal (Usuli Faqih Research Centre, USIM, 2015)
This study presents the evaluation procedures of Arabic vocabulary courseware namely Arabiyyatiy for non-Arabic students at the beginner’s level. This study employs an evaluative method in conducting its research procedures. 40 level one students from the Center for Foundation Studies, International Islamic University Malaysia had participated in the study which was carried out during the semester two of 2012/2013 academic year. The results of the vocabulary tests also show the success of multimedia program in the process of teaching and learning Arab vocabulary, since most of the students obtained good results in their post-tests conducted throughout the study. The study concludes that multimedia program can be used by all non-Arabic students regardless of their categories and backgrounds.